2020
DOI: 10.1016/j.ijscr.2020.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumor of the excluded stomach after Roux-en-Y gastric bypass: A case report and literature review

Abstract: Highlights This is the second reported case of GIST post-RYGB. GISTs generally present good prognosis after surgical resection. The case reported after RYGB did not present the patient follow-up. The case reported after gastric banding presented recurrence 3 years after resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Previous studies have identified GISTs in postop bariatric patients, though these were either c-kit-negative tumors, or after bariatric surgery other than RYGB. 2-4 Our case is deemed significant as it presents as one of the few c-kit + GISTs arising from the excluded stomach remnant post-RYGB to be described in the literature.…”
Section: Brief Reportmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have identified GISTs in postop bariatric patients, though these were either c-kit-negative tumors, or after bariatric surgery other than RYGB. 2-4 Our case is deemed significant as it presents as one of the few c-kit + GISTs arising from the excluded stomach remnant post-RYGB to be described in the literature.…”
Section: Brief Reportmentioning
confidence: 92%
“…There are currently only three reported cases of GISTS after Rouxen-Y gastric bypass (RYGB) surgery. [2][3][4] In this case report, we present a patient with a history of RYGB who developed a GIST in the excluded stomach remnant.…”
Section: Brief Reportmentioning
confidence: 99%